Working memory, processing speed, and set-shifting in children with developmental coordination disorder and attention-deficit-hyperactivity disorder - Piek, Jan; Dyck, Murray; Francis, Mona; Conwell, Alistair (Mac Keith Press, 2007)
It has been suggested that the high levels of comorbidity between attention-deficit-hyperactivity disorder (ADHD) and developmental coordination disorder (DCD) may be attributed to a common underlying neurocognitive mechanism. This study assessed whether children with DCD and ADHD share deficits on tasks measuring working memory, set-shifting, and processing speed. A total of 195 children aged between 6 years 6 months and 14 years 1 month (mean 10y 4mo [SD 2y 2mo]) were included in this study. A control group (59 males, 79 females), a DCD group (12 males, six females), an ADHD-predominantly inattentive group (16 males, four females), and an ADHD-combined group (15 males, four females), were tested on three executive functioning tasks. Children with DCD were significantly slower on all tasks, supporting past evidence of a timing deficit in these children. With few exceptions, children with ADHD did not perform more poorly than control children. These findings demonstrate the importance of identifying children with motor deficits when examining tasks involving a timing component.